How Does Happiness Influence the Loyalty of Karate Athletes? A Model of Structural Equations From the Constructs: Consumer Satisfaction, Engagement, and Meaningful - Núñez-Barriopedro, Estela; Cuesta-Valiño, Pedro; Gutiérrez-Rodríguez, Pablo; Ravina-Ripoll, Rafael (Frontiers in Psychology, 2021)
The number of federated members remains constant in recent years. Then, federations are concerned about attracting new sportsmen and women and increasing the number of members. The purpose of this research was to describe karate federations' strategies for attracting and retaining members through happiness. The analysis was carried out by designing a Structural equation modeling (SEM), which allowed to analyze the main variables which influenced the happiness of the karate athlete and consequently to study their effect on people's loyalty to sports federations. In particular, Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied in an overall model when it was possible to understand the happiness role in relation with other traditional relevant variables on loyalty. The data were obtained through primary sources by means of a survey sent to the autonomous federations in the discipline of karate, obtaining a sample of 682federated members in Spain. The results of the model revealed that consumer satisfaction, engagement, and meaningful influence on consumer happiness, but engagement was the most important and relevant variable for affecting this variable. Finally, consumer satisfaction and consumer happiness were influencing on loyalty, and consumer satisfaction was the most important variable, but consumer happiness showed as a real alternative for improving loyalty in karate sports federations. Then, one of the implications of this work was that it helped to explain how the federations can be managed to achieve loyal consumers together with a more considerable increase in the number of federated members.